The angle stabilization system of the self-balancing robot - Chernysh, H.O.; Savenko, O.S. (Reporter of the Priazovskyi State Technical University. Section: Technical sciences, 2023)
The article is devoted to the consideration of the tilt angle stabilization system of a self-balancing robot. The object of research is self-balancing robots, and the subject is systems for stabilizing their tilt angle. A comprehensive analysis of the principles and algorithms used to ensure the stability of the robot when the tilt angle is changed is presented. The technical solutions underlying the stabilization system were studied and their effectiveness in relation to maintaining the robot in a vertical position was analyzed. A mathematical model is presented in which the self-balancing robot is represented as an inverted pendulum, i.e. a two-wheeled vehicle balances itself in a vertical position relative to the ground. It is assumed that the structure moves without friction. The main equations describing the movement of the balancing robot, taking into account the dynamics of the pendulum and the wheel, were obtained. As a regulator, the LQR regulator is proposed, which provides optimal control of a closed-loop system. The workability of the model and the proposed stabilization system was verified using simulation modeling. As a result of simulated modeling, oscillograms were obtained, which demonstrate that after an exciting effect, the system stabilizes and enters an equilibrium state. A controllability test was performed, which showed that the proposed controller can effectively control the system. Controllability ensures that a system can be subjected to a control signal in order to achieve the desired behavior. An example of the practical implementation of the robot and selected main components are presented Стаття присвячена розгляду системи стабілізації кута нахилу самобалансуючого робота. Об'єктом дослідження є самобалансуючі роботи, а предметом – системи стабілізації їхнього кута нахилу. Розглянуті принципи роботи та розвиток алгоритмів, які дозволяють роботу автоматично підтримувати стабільність при зміні кута нахилу. У статті проаналізовані різні рішення, що використовуються для створення системи стабілізації, і їхні переваги та недоліки. Наведена математична модель, у якій самобалансуючий робот представлений як перегорнутий маятник, тобто двоколісний транспортний засіб врівноважує себе у вертикальному положенні відносно землі. У якості регулятора запропонований LQR-регулятор, який забезпечує оптимальне керування замкнутою системою. Працездатність моделі та запропонованої системи стабілізації перевірені за допомогою імітаційного моделювання. Наведений приклад практичної реалізації робота та обрані основні компоненти